2002
DOI: 10.1007/s00267-002-2749-9
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Workshop as a Means of Improving Communication Between Holders of Traditional and Scientific Knowledge

Abstract: Traditional ecological knowledge (TEK) and the information and insights it offers to natural resource research and management have been given much attention in recent years. On the practical question of how TEK is accessed and used together with scientific knowledge, most work to date has examined documentation and methods of recording and disseminating information. Relatively little has been done regarding exchanges between scientific and traditional knowledge. This paper examines three workshop settings in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…Nonetheless, it took years for many of the crews to recover and acquire new equipment. By any reckoning, it was an extraordinary event (Huntington et al, 2001(Huntington et al, , 2002Norton, 2002;K. Toovak, Sr., pers.…”
Section: : Catastrophic Breakupmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it took years for many of the crews to recover and acquire new equipment. By any reckoning, it was an extraordinary event (Huntington et al, 2001(Huntington et al, , 2002Norton, 2002;K. Toovak, Sr., pers.…”
Section: : Catastrophic Breakupmentioning
confidence: 99%
“…It is based on years of discussions with Iñupiat hunters and our direct experience of over 20 years of camping and conducting research on the shorefast ice. We also draw from formal oral history interviews, from archival research, and from two case studies developed for and discussed during the Barrow Symposium on Sea Ice, held in October-November 2000 (Huntington et al, 2001(Huntington et al, , 2002Norton, 2002). In that symposium, Iñupiat hunters and sea-ice researchers discussed their respective understandings of the sea-ice environment and its implications for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural models are conceptual frameworks or "pre-supposed, taken-for-granted models of the world that are widely shared (although not to the exclusion of other, alternative models) by members of a society and that play an enormous role in their understanding of that world and their behavior in it" (Quinn and Holland, 1987:4). Understanding of cultural models may help user groups, managers, and biologists to better frame perspectives, facilitate negotiation, and foster collective action to support management actions responsive to socioeconomic and ecological sustainability issues (Huntington et al, 2002;Paolisso, 2002;Stone-Jovicich et al, 2011). Findings of this study were originally reported in detail in Simeone et al (2011).…”
Section: Copper River Salmon Fisheries User Groups and Study Objectmentioning
confidence: 62%
“…Although ethnographic studies have long been an important anthropological research tool, it is perhaps the development of ''human dimensions'' studies that has facilitated an understanding of the value of local knowledge, specifically ''traditional ecological knowledge'' (TEK) as a complement to ''scientific'' knowledge (e.g., Fox 2003;Huntington et al 2004;Huntington 2005). Furthermore, in recent times, much valuable groundwork has been laid for the gathering of such knowledge (e.g., Berkes 1993;Wenzel 1999;Huntington et al 2002;Krupnik and Jolly 2002;George et al 2004;Oozeva et al 2004).…”
Section: Multivariate Time Plots Aid the Integration Of Datamentioning
confidence: 99%